2019
DOI: 10.4103/jfmpc.jfmpc_584_19
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curcumin-based and clotrimazole vaginal cream in the treatment of vulvovaginal candidiasis

Abstract: Background:Vulvovaginal candidiasis (VVC) is the second most common infection of the lower female genital among women passing through their productive age. Furthermore, Candida albicans is the most common VVC agents followed by, non-albicans Candida species. Nowadays, extensive studies are being conducted on alternative therapies and the use of herbal medicines.Objectives:The present study was conducted to compare the effect of curcumin and clotrimazole vaginal cream in the treatment of VVC.Methods:The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The co-administration of antifungal agents is effective in increasing the pharmacological effect but can cause adverse effects, such as vulvovaginal burning sensation, reported after the topical administration of CUR, as well as irritation, burning, and itching with the application of MCZ. However, when the effect of the combined drugs is synergistic, the doses can be reduced and, consequently, the adverse effects resulting from both drugs can be minimized [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The co-administration of antifungal agents is effective in increasing the pharmacological effect but can cause adverse effects, such as vulvovaginal burning sensation, reported after the topical administration of CUR, as well as irritation, burning, and itching with the application of MCZ. However, when the effect of the combined drugs is synergistic, the doses can be reduced and, consequently, the adverse effects resulting from both drugs can be minimized [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ninety-four women with VVC were studied and divided into two groups: those taking a 10% vaginal cream with curcumin and a 1% clotrimazole-based vaginal cream. It was observed that vulvar and vaginal pruritus was reduced in both groups: after clotrimazole, from 87.2% to 19.1%; after curcumin, from 85.1% to 12.8% [58].…”
Section: Herbal Preparations Used To Treat the Vagina And Vulvamentioning
confidence: 86%
“…The most expressive example is curcumin. A complete cure of VVC in women using turmeric cream was observed in 66% of patients, whereas after clotrimazole, the result reached 48.9% [58]. This is probably caused by the fact that curcumin reduces the induction of multiple inflammatory mechanisms of cyclooxygenase 2 and interleukins Il-1, -5, -6, -12, and -18 and lox-12.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation